2021
DOI: 10.1016/j.jsps.2021.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotechnical and analytical preformulation studies for cannabidiol orodispersible tablets

Abstract: Obtaining orodispersible tablets (ODT) containing substances from the second Biopharmaceutical Class has raised concerns as the dissolution test is challenging. This study aimed to select suitable excipients for developing orodispersible tablets containing cannabidiol (CBD) by direct compression method. No similar studies were found in the literature. Excipients from different classes were characterized using the SeDeM-ODT tool: fillers – lactose (LCT) and microcrystalline cellulose (CelMC), sweeteners – sorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
3
9
0
Order By: Relevance
“…These two speci c bands have also been observed in previous study of Andriotis et al in their CBD/cyclodextrin formulation and cannabidiol orodispersible tablets formulated by Vlad et al [23,24]. In this work, the peaks of CBD were observed in PCL NPs-4 sample more profoundly than in PCL NPs-1, 2, 3.…”
Section: Ftir Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…These two speci c bands have also been observed in previous study of Andriotis et al in their CBD/cyclodextrin formulation and cannabidiol orodispersible tablets formulated by Vlad et al [23,24]. In this work, the peaks of CBD were observed in PCL NPs-4 sample more profoundly than in PCL NPs-1, 2, 3.…”
Section: Ftir Analysissupporting
confidence: 86%
“…The stretching vibration caused by the OH group was present in all CBD-loaded PCL NPs at bands 2860 cm -1 and 2945 cm -1 . The band at 1442 cm -1 , attributed to the deformation of methylene or methoxy groups (C-H deformation), cannot be considered as a representative band for CBD [23]. The presence of CBD within PCL can be emphasized by comparing the PCL bands with the presence of bands belonging to aliphatic groups (= C-H) at 1585 cm -1 and 1628 cm -1 .…”
Section: Ftir Analysismentioning
confidence: 99%
“…The 2 θ angle values characteristic for CBD are 9.66°, 10.24°, 11.78°, 12.53°, 13.08°, 15.34°, 19.85°, 19.03°, 21.66°, 22.73°, 23.79°, 25.29°, 26.42°, 29.19° with the highest intensity occurring in the case of 9.66°. 23 Lv et al 24 reported similar observations on the XRD pattern of pure crystalline CBD. Fig.…”
Section: Resultssupporting
confidence: 53%
“…A 10 mg CBD orodispersible tablet (CBD-ODT) has been developed using Quality by Design (QbD) principles to optimize formulation parameters such as disintegration time, crushing strength, friability, and the release profile of the API at different intervals (Figure 3). Independent variables, including the choice of solid carriers, were carefully considered [84,85]. However, a significant challenge encountered in developing ODT with CBD is the in vitro dissolution test, owing to the API s low solubility in water-based media.…”
Section: Ongoing Research and Preclinical Trialsmentioning
confidence: 99%